Effects of the non-perturbative mode structure on energetic particle transport. (8th April 2020) - Meng, G.; Lauber, Ph.; Lu, Z.; Wang, X.
Abstract: Energetic particles (EPs) are known to change the properties of shear Alfvén waves in tokamaks, and for this reason non-perturbative models have to be used to describe their linear and non-linear evolution. In this work, mode structures distortion with symmetry breaking properties featured by a finite radial wave phase velocity due to EP effects are considered. A mode structure of the form A ( s ) = e − σ ( s − s 0 ) 2 with complex parameters σ and s 0 is used, to describe not only the width ( ∝ 1 / Re σ ) and the mean location (Re s 0 ) of the bell-shaped radial structure, but also the radial phase variations (Im σ , Im s 0 ), where s is the normalized radial coordinate. The values of ( σ, s 0 ) are fitted from the results given by the gyrokinetic eigenvalue code LIGKA. The impact on EP transport is investigated using the drift-kinetic code HAGIS. The effects of the mode structure symmetry breaking on the mode saturation level and the EP transport are analysed. In the presence of mode structure symmetry breaking which is relevant to the simulation and experimental observations, the growth rate as well as the particle and energy transport level can vary by ∼10%. The velocity-space averaged parallel velocity of EPs in the inner region s = 0.2 ∼ 0.5 can change its sign for different mode structures, demonstrating the importance of the mode structure symmetry breaking on EP toroidal velocity reversal. This large effect (∼100%) on the mean parallel flow could have implications for EP current drive and the transport in the burning plasmas.